Knowledge and Practice of Early Childhood Caries among Pediatricians and Gynecologists - Sundas, Sunanda; Sah, Barun Kumar; Dhakal, Neha; Joshi, Neera; Pariyar, Jitendra (Journal of Karnali Academy of Health Sciences, 2021)
Background: Early Childhood Caries (ECC) damages the tooth, adversely affects oral cavity and general health. Gynecologists and pediatricians regularly visited by mothers during antenatal and after childbirth have important role in prevention of ECC.Methods: A cross sectional quantitative study was conducted among gynecologists and pediatricians working in various hospitals of Nepal from January 15 to March 15, 2020. The self-validated questionnaire consisted questions on demographic details, knowledge, attitude, and practices of respondents on ECC. The responses were tabulated and analyzed.Results: Total 205 out of which 132 gynecologists and 73 pediatricians participated in the study. Seventyfour percent of pediatricians examined teeth for cavities, 88 % suggest brushing twice daily and 83% referred children with oral diseases and dental caries to pediatric dentist. Majority (78%) of the respondents knew dental caries as an infectious disease and 91% thought untreated dental disease could cause systemic complications. About half (54.7%) answered first year to be ideal for the first dental visit, 51.3% thought dental visit should be every six monthly and 71.2% counselled children and parents on the importance of tooth brushing. Only 24% and 34% participants were aware of vertical transmission of bacteria and child born to a pregnant woman with dental caries could have ECC respectively. Ninety-four percent of the practitioners feel that they have a role in prevention of oral diseases. Realizing the importance, 83% of pediatricians and gynecologists desire to take oral health training.Conclusions: Moderate knowledge and attitude about childhood caries is reported among a sample of Nepalese gynecologists and pediatricians which signifies the importance of oral health training among these groups of practitioners.